Selected Lectures of the Meeting "Rare diseases: diagnostic pathways and new therapies", including the session on the Life MILCH project and the session titled "They will be famous"; Cagliari (Italy); October 18, 2023 - - (Hygeia Press di Corridori Marinella, 2023)
Selected Lectures of the Meeting "Rare diseases: diagnostic pathways and new therapies", including the session on the Life MILCH project and the session titled "They will be famous"; Cagliari (Italy); October 18, 2023 The Meeting "Rare diseases: diagnostic pathways and new therapies", including the session on the Life MILCH project and the session titled "They will be famous", is a Satellite Meeting of the 19th International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 18th-21st, 2023. LECT 1. NEONATAL ONSET OF GENETIC SYNDROMES • S. Giglio (Cagliari, Italy) LECT 2. GENETIC CHOLESTATIC LIVER DISORDERS: IS IT TIME TO CHANGE THEIR MANAGEMENT? • G. Maggiore (Rome, Italy) LECT 3. WILSON DISEASE • G. Loudianos (Cagliari, Italy) LECT 4. HEMOLYTIC-UREMIC SYNDROME • N. Lepori, A. Atzeni, A. Angioi, M. Floris, G. Cabiddu, A. Pani (Cagliari, Italy) LECT 5. DIAGNOSIS AND THERAPEUTIC APPROACHES TO SPINA BIFIDA: A COMPREHENSIVE REVIEW • G. Masnata (Cagliari, Italy) LECT 6. NEUROLOGICAL MANIFESTATIONS OF NEUROFIBROMATOSIS TYPE 1 • C. Soddu (Cagliari, Italy)  LECT 7. SYDENHAM'S CHOREA: UPDATE ON DIAGNOSIS AND THERAPY • T. Foiadelli (Pavia, Italy) LECT 8. EPILEPTIC ENCEPHALOPATHIES • D. Pruna, S. Cossu, M. Asunis, S. Dettori, F. Banditelli, M. Balzarini (Cagliari, Italy) LECT 9. SYNDROMIC DEAFNESS • S. Savasta (Cagliari, Italy) LECT 10. METABOLIC MYOPATHIES • M. Balzarini (Cagliari, Italy) LECT 11. PREVIEWS OF THE MILCH STUDY IN A CHANGING PLANET • P. Palanza, V. Fanos, A.M. Papini, M.E. Street (Parma, Cagliari, Sesto Fiorentino and Reggio Emilia, Italy) LECT 12. THE FIRST COMPREHENSIVE DIAGNOSTIC PROFILE OF SPECIFIC METABOLITES OF EDCs (PHTHALATES, BISPHENOLS, PARABENS, PYRETHROIDS, PAHS, AND POLAR PESTICIDES) IN MOTHER AND CHILD DYADS: NEWS FROM THE LIFE MILCH PROJECT • F.R. Fernandez, F. Nuti, P. Palanza, M.E. Street, V. Fanos, A.M. Papini (Sesto Fiorentino, Parma, Reggio Emilia and Cagliari, Italy) LECT 13. THE IMPACT OF ENDOCRINE DISRUPTORS: WHICH CONSEQUENCES? • M.E Street, P. Palanza, V. Fanos, A.M. Papini (Parma, Reggio Emilia, Cagliari and Sesto Fiorentino, Italy) LECT 14. PLASTIC AND BREASTFEEDING • A. Ragusa (Rome, Italy) LECT 15. THE CRISIS IN THE CRITICAL SITUATION • E.M. Oppedisano, G. Melis, F. Sau, G. Cherchi (Cagliari, Italy) LECT 16. AN UNUSUAL DYSPNEA, NEVER FALL FOR A DIAGNOSIS • M. Casadio, G. Colucci, G. Cherchi (Cagliari, Italy) LECT 17. BEWARE OF THE CAT • G. Casti, S. Marras, R. Basile, M. Zanda, G. Cherchi (Cagliari, Italy)